Macro-fungi of Karhiya Community Forest, western Terai, Nepal - Aryal, Hari Prasad; Budathokio, Usha (Nepalese Journal of Biosciences, 2013)
This is the preliminary report on mycological investigation carried out at Karhiya Community Forest, in Terai region of western Nepal. Phytogeographycally, the area lies within a narrow limit of altitude between 160 and 195 msl in tropical deciduous riverine forest, where major dominant species of macro fungi are Amanita chepangiana, A. caesrea, A. pantherina, Macrolepiota procera, M. rhacodes, Marasamius perforans, M. oreades, Termitomyces clypeatus and T. eurhizeus. The samples collected in the present study represented 26 genera of Basidiomycetes belonging to 18 families and 30 species. The dried specimens are housed in the Nepalese herbaria (TUCH, Kath). The area embraces the mycophagus ethnic communities like Tharu, Magar, Kumal, Majhi, Thakali, Gugung, Girel and Chhantal. The mycoelements prevailing in this area need sustainable utilization and conservation. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7495 Nepalese Journal of Biosciences 2 : 93-97 (2012)